2012
DOI: 10.1177/0091270011416938
|View full text |Cite
|
Sign up to set email alerts
|

Tigecycline Pharmacokinetics in Subjects With Various Degrees of Renal Function

Abstract: The pharmacokinetic parameters of tigecycline were assessed in subjects with severe renal impairment (creatinine clearance <30 mL/min, n = 6), subjects receiving hemodialysis (4 received tigecycline before and 4 received tigecycline after hemodialysis), and subjects with age-adjusted, normal renal function (n = 6) after administration of single 100-mg doses. Serial serum and urine samples were collected and assayed using validated liquid chromatography with tandem mass spectrometer (LC/MS/MS) methods. Concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 16 publications
3
21
1
2
Order By: Relevance
“…The primary parameters, V c and Cl were in agreement with those reported previously (Kuti, Dowzicky, & Nicolau, ; Muralidharan et al, ; Rubino et al, ; Van Wart et al, ). The plasma AUC 0–12 in our study (4713 h ng/mL) was also similar to previous reports (Korth‐Bradley et al, ; Muralidharan et al, ). The mean V csf (0.173 L) was similar to the physiological volume of the CSF (about 0.2–0.3 L) and was consistent with a previous study (Li et al, ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The primary parameters, V c and Cl were in agreement with those reported previously (Kuti, Dowzicky, & Nicolau, ; Muralidharan et al, ; Rubino et al, ; Van Wart et al, ). The plasma AUC 0–12 in our study (4713 h ng/mL) was also similar to previous reports (Korth‐Bradley et al, ; Muralidharan et al, ). The mean V csf (0.173 L) was similar to the physiological volume of the CSF (about 0.2–0.3 L) and was consistent with a previous study (Li et al, ).…”
Section: Resultssupporting
confidence: 93%
“…Symmetrical peak shape and suitable retention time were obtained by gradient elution conditions. To the best of our knowledge, trifluoroacetic acid was used in the majority of reported studies (Ji et al ., , ; Korth‐Bradley et al, ; Rodvold et al, ). Other researchers have used formic acid (Conte et al ., ; Ozcimen et al ., ) and 90% 10 m m ammonium formate (Chen et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently published papers suggest that the doses should be increased to improve treatment efficacy in comparison to the currently recommended dose [23][24][25]. A relatively high degree of protein binding (71-78%) and a large volume of distribution (V ss > 900 L) theoretically decreases the elimination of this antibiotic through CRRT [26]. To date there have been no studies on the adsorption of tigecycline on the filter membranes used for CRRT.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies (17)(18) found no significant change in the tigecycline pharmacokinetics in patients with impaired renal function, and tigecycline was not cleared by dialysis. There is no need to adjust the dose in patients with impaired renal function or in patients undergoing hemodialysis treatment (11).…”
Section: Figmentioning
confidence: 99%